Survey of ICT and Education in Africa : Gabon Country Report - Fall, Babacar (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev)-supported survey of Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Gabon has opted to set up a national system for general access to information using computer related technologies. However, there is currently no plan in the education system to incorporate ICT into the administrative and teaching domains. Of course, the need to computerize schools is becoming urgent, but the initiatives required to address this need are considerable. A plan for managing computers, from the National Ministry of Education, has been in development since 2006.